PERENCANAAN LANSKAP DENGAN PENDEKATAN COMMUNITY BASED TOURISM PADA KAWASAN DERMAGA KETAPANG - Naafil Wihandono; Rian Adetiya Pratiwi; Ina Winiastuti Hutriani (Program Sarjana Arsitektur Universitas Internasional Batam, 2024)
Dermaga Ketapang in Dusun Ketapang Barat, with a land area of 10 hectares and a population of 438 people, has a significant tourism potential. It serves as an important transit point for tourists heading to Pahawang Island and other islands in Pesawaran Regency. Dusun Ketapang Barat has potential in community-based tourism due to its majority of residents working in the tourism sector and has several active local communitiesinvolved in tourism activities. The Pesawaran Regency Government has designated this area as a coastal, culinary, and creative economy-based tourism zone. However, these potentials are faced with challenges such as inadequate infrastructure, disorganized spatial planning, and a lack of distinctive characteristics for Dusun Ketapang Barat as a tourism area. To address these issues, a landscape planning with community based tourism needs to be conducted. This research aims to identify potentials and problems as well as develop a community-based tourism landscape planning approach for Dermaga Ketapang area. This research used the Gold method, consisting of preparation, site data collecting, site data analysis, planning principles, and a masterplan. Identification and analysis of potentials and issues results in five planning principles: infrastructure improvement, small-scale economic zone creation, development of existing areas with community-based tourism principles, training for the local tourism community, and the development of distinctive products. These principles developed into development plans resulting in a masterplan and 3D visualization of the landscape planning for the Dermaga Ketapang area in Dusun Ketapang Barat.